Cerebral palsy - Chandrashekar SS (Journal of All India Institute of Speech and Hearing, 1973)
It implies that the definitory process should precede a discussion. Hence, before starting a discussion concening the existence of the condition of 'Cerebral Palsy' it looks obvious at this stage to give out the definition of 'Cerebral Palsy'. However, it should be remembered that 'too great a haste in defining is almost as failure to define at all' (Coreignton).